Screening of new inbreds for their sterility and fertility reaction against new CMS lines in sunflower (Helianthus annuus L.): Screening of new inbreds for their sterility and fertility reaction against new CMS lines in sunflower (Helianthus annuus L.) - S NEELIMA; K ASHOK KUMAR; K VENKATARAMANAMMA (Journal of Oilseeds Research, 2020)
Sunflower, an important oilseed crop in the state of Andhra Pradesh witnessed a sharp decline in area during the recent past and the lack of diversity in CMS lines and inbreds is attributed as one of the major reasons. To address this issue, a set of new CMS lines (NDLA 2,3,4,5,6,7,8) and inbreds (CPI 1,6,8,10, NDI 1, 2, 12, 13, 14) of sunflower were tested. The results revealed that NDI 2 showed maintainer action whereas NDI 14, 15 segregated for fertility. CPI 1, 6, 8, 10 and NDI 1, 13 restored fertility. The identified restorers can be exploited either to strengthen the future hybrid breeding or in the synthesis of new restorers.